2011
DOI: 10.1021/jp205347s
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Equilibrium Constants for the Reaction between Acetone and HO2 Using Infrared Kinetic Spectroscopy

Abstract: The reaction between the hydroperoxy radical, HO(2), and acetone may play an important role in acetone removal and the budget of HO(x) radicals in the upper troposphere. We measured the equilibrium constants of this reaction over the temperature range of 215-272 K at an overall pressure of 100 Torr using a flow tube apparatus and laser flash photolysis to produce HO(2). The HO(2) concentration was monitored as a function of time by near-IR diode laser wavelength modulation spectroscopy. The resulting [HO(2)] d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 34 publications
4
32
1
Order By: Relevance
“…Numerous experimental and theoretical studies of reversible addition of HO 2 to various carbonyl‐containing compounds have been conducted . Perusal of the available data shows that our derived values for K 3 , k 3 , and k −3 are reasonable (ie, of similar magnitude to those previously reported).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Numerous experimental and theoretical studies of reversible addition of HO 2 to various carbonyl‐containing compounds have been conducted . Perusal of the available data shows that our derived values for K 3 , k 3 , and k −3 are reasonable (ie, of similar magnitude to those previously reported).…”
Section: Resultssupporting
confidence: 78%
“…The mechanism described here, involving an alcohol (RCH 2 OH), the corresponding carbonyl compound (RCH=O), and the interactions of these species with OH and/or HO 2 , is not unique to the HYAC/MGLY pair, but in fact is generally applicable: Numerous experimental and theoretical studies of reversible addition of HO 2 to various carbonyl-containing compounds have been conducted. 28,33,40,47,52,53 Perusal of the available data shows that our derived values for K 3 , k 3 , and k −3 are reasonable (ie, of similar magnitude to those previously reported). Our derived equilibrium constants for the HO 2 /MGLY system fall intermediate between those previously reported for HCHO and CH 3 CHO, 28,37-39 and thus represent one of the stronger HO 2 /carbonyl interactions identified to date.…”
Section: Atmospheric Implicationssupporting
confidence: 85%
See 2 more Smart Citations
“…From such experiments, i.e., the observation of the overall loss of HO 2 radicals through establishing the equilibrium (R1), it is not possible to distinguish between (R1a) and (R1b). In a recent work on the possible corresponding equilibrium reaction between acetone and HO 2 radicals , experimental evidence has been found that only the corresponding complex formation (R1a) takes place and that the subsequent rearrangement (R1b) to formation of the peroxy radical is too slow. In the case of CH 2 O, however, the fast establishment of the equilibrium (R1b) is supported from earlier experiments by end‐product studies , ESR detection of the HOCH 2 O 2 radicals as well as UV‐absorption studies .…”
Section: Resultsmentioning
confidence: 99%